Social media, disinformation, and regulation of the electoral process: a study based on 2018 Brazilian election experience - Santos, Gustavo Ferreira (Revista de Investigações Constitucionais, 2020)
There is global concern about the impact that ‘fake news’ has on democratic decision-making processes. Democratic decision-making needs to be well informed and voters need a minimum of confidence in the information they receive about competitors. The Internet has increased the availability of information, but has allowed new ways of manipulating it to emerge. In recent electoral experiences, social media has increased the impact of misinformation on democracy. These experiences have shown us that Internet governance during the election campaign is an urgent issue. A laissez-faire approach to the electoral process is a threat to democracy because it allows all kinds of cheating. Institutions responsible for ensuring the integrity of elections need to try democratic resources to constrain competitors to behave responsibly. It is important to know the concrete experience of a country that has suffered the attack of disinformation campaigns during an election period, studying the action of the body responsible for organizing this process. This article discusses the guarantee of the electoral process based on the case study of the 2018 Brazilian election.